Political Identity and Financial Risk Taking: Insights from Social Dominance Orientation - Han, Kyuhong; Jung, Jihye; Mittal, Vikas; Zyung, Jinyong Daniel; Adam, Hajo (Journal of Marketing Research, 2019)
This article investigates how people’s political identity is associated with their financial risk taking. The authors argue that conservatives’ financial risk taking increases as their self-efficacy increases because of their greater social dominance orientation, whereas liberals’ financial risk taking is invariant to their self-efficacy. This central hypothesis is verified in six studies using different measures of political identity, self-efficacy, and financial risk taking. The studies also use different samples of U.S. consumers, including online panels, a large-scale data set spanning five election cycles, and a secondary data set of political donations made by managers at companies. Finally, the authors articulate and demonstrate the mediating effect of individuals’ focus on the upside potential of a decision among conservatives but not liberals.